1994
DOI: 10.1046/j.1471-4159.1994.62051894.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Peripherin Dimer: Changes During Axonal Development and Regeneration of the Rat Sciatic Nerve

Abstract: Western blotting of rat dorsal root ganglion (DRG) and sciatic nerve under nonreducing conditions revealed that a peripherin‐specific antibody recognized a protein species of 116/130 kDa, pi 5.6, in addition to peripherin (56 kDa, pl 5.6). We showed that this 116/130 kDa protein is a disulfide dimer of peripherin, because it gave rise to a single protein band comigrating with peripherin under reducing conditions and yielded the same proteolytic pattern as peripherin upon N‐chlorosuccinimide digestion. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…2A). The intermediary filament peripherin is present in all small axons and re-expressed during nerve regeneration (20,21). At 7 days after injury, small degenerated axons with stained granules persisted in the nerves of vehicle-treated animals, although in etifoxinetreated animals a large number of linear peripherinimmunoreactive axons was observed at this stage (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…2A). The intermediary filament peripherin is present in all small axons and re-expressed during nerve regeneration (20,21). At 7 days after injury, small degenerated axons with stained granules persisted in the nerves of vehicle-treated animals, although in etifoxinetreated animals a large number of linear peripherinimmunoreactive axons was observed at this stage (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…This process could therefore sequester peripherin monomers, which would not be available for neurofilament assembly. Thus, if peripherin is involved in axonal regeneration, as previously suggested [25, 26, 61, 67, 92], the presence of CMT2B-causing mutants could be highly detrimental. Another possibility is that RAB7A binding could alter peripherin phosphorylation, either directly or indirectly.…”
Section: Discussionmentioning
confidence: 91%
“…Also, an aggregate-inducing peripherin isoform is upregulated in ALS [94]. Importantly, peripherin is thought to be important in axonal regeneration [25, 26, 61, 67, 92]. Indeed, it has been suggested that the regeneration program is at least in part based on changes to intermediate filament composition and dynamics [87, 92].…”
Section: Introductionmentioning
confidence: 99%
“…We selected the PRPH-1 gene, which is expressed predominantly in neurons of the PNS and the cranial nerves (Gorham et al 1990;Troy et al 1990a), as the basis for our reporter. PRPH-1 encodes the cytoskeletal protein peripherin and has been shown to respond to injury, increasing its expression in regenerating neurons and downregulating expression after target reconnection (Beaulieu et al 1999b;Chadan et al 1994;Gervasi et al 2003;Troy et al 1990b;Wong and Oblinger 1990). A similar induction during embryonic neural development followed by a postnatal reduction in expression suggests a role for peripherin in maintaining an elongation permissive cytoskeleton in pathfinding axons (Portier et al 1993).…”
Section: Introductionmentioning
confidence: 99%